Metamorphosis of Seaweeds into Multitalented Materials for Energy Storage Applications. Issue 19 (26th March 2019) - Shin, Myoungsoo; Song, Woo‐Jin; Han, Jung‐Gu; Hwang, Chihyun; Lee, Sangyeop; Yoo, Seokkeun; Park, Sewon; Song, Hyun‐Kon; Yoo, Seungmin; Choi, Nam‐Soon; Park, Soojin
Abstract: Transition metal ion dissolution due to hydrofluoric acid attack is a long‐standing issue in the Mn‐based spinel cathode materials of lithium‐ion batteries (LIBs). Numerous strategies have been proposed to address this issue, but only a fragmentary solution has been established. In this study, reported is a seaweed‐extracted multitalented material, namely, agar, for high‐performance LIBs comprising Mn‐based cathode materials at a practical loading density (23.1 mg cm −2 for LiMn2 O4 and 10.9 mg cm −2 for LiNi0.5 Mn1.5 O4, respectively). As a surface modifier, 3‐glycidoxypropyl trimethoxysilane (GPTMS) is employed to enable the agar to have different phase separation behaviors during the nonsolvent‐induced phase separation process, thus eventually leading to the fabrication of an outstanding separator membrane that features a well‐defined porous structure, superior mechanical robustness, high ionic conductivity, and good thermal stability. The GPTMS‐modified agar separator membrane coupled with a pure agar binder to the LiNi0.5 Mn1.5 O4 /graphite full cell leads to exceptional improvement in electrochemical performance outperforming binders and separator membrane in current commercial products even at 55 °C; this improvement is due to beneficial features such as Mn 2+ chelation and PF5 stabilizing capabilities. This study is believed to provide insights into the potential energy applications of natural seaweeds. Abstract : A seaweed‐extracted multitalented biomaterial for lithium‐ion battery components including a separator membrane and binder is demonstrated as a promising material for the Mn‐based cathode materials with highly stable cycling performance (84%) even at high‐voltage operation (3.5–5.0 V) under high temperature (>55 °C) at a high charge/discharge rate (1 C/1 C).